Enhanced dry deposition of nitrogen pollution near coastlines: A case study covering the Chesapeake Bay estuary and Atlantic Ocean coastline. Issue 23 (10th December 2016) - Loughner, Christopher P.; Tzortziou, Maria; Shroder, Shulamit; Pickering, Kenneth E.
Abstract: Atmospheric deposition of nitrogen pollution is one of the major sources of nitrogen to many terrestrial and aquatic ecosystems, worldwide. This modeling study suggests that coastlines frequently experience disproportionally high dry deposition of reactive nitrogen. High concentrations of air pollution from coastal cities often accumulate over adjacent estuaries and coastal waters due to low dry deposition rates over the water and a shallow marine boundary layer trapping marine emissions. As high concentrations of pollutants over the water are transported inland, enhanced dry deposition occurs onshore along the coastlines. Large spatial gradients in air pollutants and deposition totals are simulated along the coastline with decreasing concentrations/deposition as the distance from the water increases. As pollutants are transported onshore, air pollution mixing ratios near the surface decrease due to removal by dry deposition, vertical dilution due to deeper mixing layer heights, and decrease in friction velocity as a function of distance inland from the coastline. Ammonium nitrate formation near agricultural ammonia sources, sodium nitrate formation near coastal areas with atmospheric sea‐salt loadings, and particulate growth via water uptake also contribute to large nitrate dry deposition totals at the coastline. Gradients in dry N deposition are evident over a monthly time scale and are enhanced during sea and bay breeze events. Current existing N‐deposition monitoring networks do not capture the large spatial gradients of ammonium, nitrate, and nitric acid concentrations near coastlines predicted by the model due to the coarse spatial density distribution of monitoring sites. Key Points: Air quality model simulates enhanced dry deposition of nitrogen pollution along coastlines Sea and bay breezes magnify nitrogen dry deposition gradient along coastlines